The Influence of Brand Image and Brand Trust on the Decision to Purchase XL Axiata Data Packages in Pontianak - Gentar Pardeanto; Samsuddin Samsuddin (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to determine the effect of brand image and brand trust on purchasing decisions for XL Axiata data packages in Pontianak City. The background of this study is the rapid development of the telecommunications industry, the importance of consumer perceptions of brands, and increasingly tight competition between service providers. This study uses a quantitative approach with 100 respondents selected through a purposive sampling method. Data were collected through questionnaires and analyzed using validity, reliability, classical assumptions, and multiple linear regression tests with the SPSS version 25.0 application. The results showed that brand image and brand trust had a significant and positive effect on purchasing decisions. Brand image was measured through indicators of identity, personality, association, and brand behavior, while brand trust was assessed based on brand characteristics, company credibility, and friendship between consumers and brands. The regression results showed a correlation value of R = 0.718, which means a strong relationship, and a determination coefficient value of R² = 0.515, which means that both variables explain 51.5% of the variation in purchasing decisions. The results of the t-test show that brand image (t = 4.346; sig. = 0.000) and brand trust (t = 3.418; sig. = 0.001) have a significant partial effect. The F test (F = 32.912; sig. = 0.000) proves that there is a simultaneous effect.y offers a unique perspective on community-driven poverty alleviation strategies.